CHANGES IN THE VALUE OF QUALITY INDICATORS IN THE CAPITATION FORMULA FOR PRIMARY HEALTH CARE IN SERBIA DURING THE PANDEMIC - Medarević, Aleksandar; Ninković, Olivera; Simonović, Periša; Vasić, Milena (HEALTH CARE, 2025)
Introduction/Aim. The COVID-19 pandemic created new challenges and assignments for primary care, affecting routine health services. This study aimed to measure the changes in the values of the performance indicators that are part of the capitation formula in Serbia using data obtained from the National Health Insurance Fund. Methods. Data were analyzed at the national level. The indicator change was measured as the absolute difference in the indicator’s values between 2020 and 2019. Results. In the healthcare services for adults, the values of three indicators related to lifestyle advice increased in 2020 between 3.0% and 3.8%, while the values of indicators related to diabetes, arterial hypertension, and among patients with previous myocardial infarction have decreased in the range of 0.5% to 2.4%. The values of indicators associated with counseling obese children, the adequate number of check-ups of newborns, and services related to early detection and counseling among pregnant women increased by 1.2% to 10.2 %. The other indicators recorded a decline in their value up to 9.9%. Conclusion. Despite the obstacles faced during the COVID-19 pandemic, primary healthcare has played and continues to play a substantial role in preserving and improving the population’s health.